Work related stressors among nurses in medical intensive care units at University hospital = (3VZhW GdYed Hjf GdeeQVGJ ai hMOGJ GdYfGjI GdeQcRI GdHGWfjI HeSJTai GdLGeYI (B/ s - Khalid Mohamed Ismail Abedelhammed; Fatma Ahmed Abed; Hanaa Youssry Hashem (Cairo : Khalid Mohamed Ismail Abedelhammed, 2016)
Background: The term stress has been commonly applied these days, being associated with sensations of discomfort, work stressors among staff nurses at medical intensive care unit are increasingly recognized as one of the most serious occupational health hazards and it has significant consequences for both staff nurses and the clinical environment (medical intensive care unit) such as psychological and physical health deterioration, decrease productivity, and impaired professional practice. The aim of the study was to explore the work related stressors among nurses at medical intensive care units at a university hospital. Descriptive exploratory design was utilized in this study. Convenient sample consisted of staff nurses. Two tools were developed by the investigator and consist of two parts for data collection: first part was related to nurses' socio-demographic data, the second part to identify work stressors among staff nurses .Results: the finding of the study revealed that the highest sources of work stressors among the studied sample at intensive care unit were: work load, lack of peer support and death and dying of patient (75.8 %; 74.2 5 & 69.7 % respectively). A stress management program for intensive care nurses is recommended
Thesis (M.Sc.) - Cairo University - Faculty of Nursing - Department of Nursing Services Administration
Issued also as CD
Keywords: Medical intensive care units; Nurses work stressors; Work stressors